EVALUASI KEBIJAKAN STANDAR PELAYANAN PADA BADAN PERIJINAN DAN PENANAMAN MODAL DAERAH PROVINSI KALIMANTAN TIMUR - Norlina . (Jurnal Paradigma (JP), 2017)
The aim of this study was to obtain and evaluate information on the Service Standards Policy BPPMD East Kalimantan province viewed from the component service standards and policies for the organization as well as the impact of the policy. While the method of analysis used by three (3) lines of activities going on simultaneously, namely data collection, Condensation, data presentation, and conclusion / verification.